Study on the monitoring method of debonding between concrete beams and reinforced steel plates based on piezoelectric smart materials - Wang, Yanru; Kong, Hu; Sun, Yaxi; Tan, Mingli; Chen, Lihua (Frontiers in Materials, 2024)
Concrete reinforcement is essential for ensuring the safety and durability of concrete structures. Bonding steel plates to reinforce concrete is widely used to renovate or strengthen concrete beam structures. Due to construction quality and the influence of factors such as environment and fatigue, debonding often occurs between the steel plate and concrete, making monitoring and early warning after concrete structure reinforcement challenging. This paper proposes a novel approach to monitor the degree of debonding between the steel plate and concrete beam using active sensing technology. The method uses lead zirconate titanate (PZT) as an actuator to generate stress waves. It prepares strip sensors with polyvinylidene fluoride (PVDF) as the sensing element to monitor stress waves passing through the steel plate and concrete beam. The monitoring system detects the degree of debonding between the steel plate and the concrete beam by monitoring the change in surface voltage of the sensor. Experiments show that the degree of debonding significantly correlates with the received voltage signal; the higher the debonding, the larger the received voltage signal. It is also observed that, at the same degree of debonding, the actuator and sensor attachment position have a particular impact on the received voltage signal. Through experiments and numerical simulation analysis, it is found that when the sensor is attached to the left side of the steel plate, that is, the bonded section of the steel plate, the amplitude of the voltage signal collected by the dynamic information acquisition system is the smallest, i.e., V_debonded section > V_middle > V_bonded section. Based on the above research, the active sensing technology proposed in this paper has good sensitivity to the degree of debonding between the steel plate and concrete. It is expected to become an effective monitoring and evaluation method for the degree of debonding between steel plates and concrete.